Counseling on the Potential of Platelet Growth Factor as a Biological Agent to Overcome Osteoarthritis Disorders at Ar-Rasyid Hospital, Palembang, Indonesia - Hidayat, Rachmat (Indonesian Community Empowerment Journal, 2023)
Growth factors are cytokines that play a role in triggering a series of inhibition of inflammatory processes and triggering the repair of joint cartilage, which acts as a shock absorber. However, the current phenomenon shows that patients are still very reluctant to take advantage of the potential of platelet growth factor as a modality for the treatment of OA. The aspect of patient ignorance regarding the potential of this modality is believed to be the reason for the lack of interest in OA patients in utilizing this therapeutic modality. This community service aims to increase the knowledge aspect of OA patients about the potential benefits and possible risks of using platelet growth factors through the counseling and education process for OA patients at Ar-Rasyid Hospital, Palembang, Indonesia. This counseling activity was carried out for outpatients at the polyclinic of Ar-Rasyid Hospital, Palembang, Indonesia. There is enhancement knowledge score for respondents after being given counseling about the potential of growth factor from platelets to treat OA, with p<0.05. The results of the study also showed that there was an increase in attitudes and behavior in choosing the modality of platelet growth factor therapy after the counseling process was carried out, with p <0.05. Counseling activities are effective in improving aspects of patient knowledge and behavior at Ar Rasyid Hospital, Palembang, Indonesia, in choosing the modality of growth factor therapy from platelets for OA.